Oral Microbiota-Driven Cell Migration in Carcinogenesis and Metastasis - Bai, Huimin; Yang, Jing; Meng, Shu; Liu, Chengcheng (Frontiers in Cellular and Infection Microbiology, 2022)
The oral cavity harbors approximately 1,000 microbial species, and both pathogenic and commensal strains are involved in the development of carcinogenesis by stimulating chronic inflammation, affecting cell proliferation, and inhibiting cell apoptosis. Moreover, some substances produced by oral bacteria can also act in a carcinogenic manner. The link between oral microbiota and chronic inflammation as well as cell proliferation has been well established. Recently, increasing evidence has indicated the association of the oral microbiota with cell migration, which is crucial in regulating devastating diseases such as cancer. For instance, increased cell migration induced the spread of highly malignant cancer cells. Due to advanced technologies, the mechanistic understanding of cell migration in carcinogenesis and cancer metastasis is undergoing rapid progress. Thus, this review addressed the complexities of cell migration in carcinogenesis and cancer metastasis. We also integrate recent findings on the molecular mechanisms by which the oral microbiota regulates cell migration, with emphasis on the effect of the oral microbiota on adhesion, polarization, and guidance. Finally, we also highlight critical techniques, such as intravital microscopy and superresolution microscopy, for studies in this field.